STUDY ON CLINICAL PROFILE AND OUTCOME IN PATIENTS WITH PERIPARTUM CARDIOMYOPATHY IN A TERTIARY CARE HOSPITAL - Dr.Parameshwara S, Dr.Mahesh Murthy B.R, Dr Eshwarappa P, Dr Harish Kumar K, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: Peripartum cardiomyopathy is a potentially fatal disease of heart failure with reducedleft ventricular ejection fraction (LVEF <45%) in a previously healthy women Despite its morbidityand mortality, the etiology